Student Perceptions of Online and Offline Learning Systems of the Economic Education Study Program of Pattimura University Ambon (Case Study of Economic Education Study Program Class of 2020) - Melkias Makely; Amjad Salong; Franklin W. Ubra (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine students' perceptions of online and offline learning systems in the Economic Education Study Program of Pattimura University, Ambon. This research uses a qualitative approach with data collection techniques in a triagulation or combined manner, the sample in this study is students of the Economic Education Study Program, Faculty of Teacher Training and Education, Pattimura University Ambon class of 2020.The total sample in this study was 15 respondents with representatives from each class of 5 respondents. From the results of this study, it was obtained that the learning system carried out online is still less effective or not good and offline learning is more effective or better, this causes students to be more inclined to like learning that is carried out offline or face-to-face in person.